Pendidikan Bisnis, Bisnis Pendidikan - Bagus Sumargo (Bina Nusantara University, 2004)
The implication of educations decentralization implies that colleges have authority to manage the whole education process. Nevertheless, the education have to be conducted professionally. The colleges should determine one study program having business oriented. Therefore, the education is driven into business purposes.